2008
DOI: 10.1136/bjo.2007.130898
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-induced choroidal damage in a murine model of retinal neovascularisation

Abstract: We show that elevated retinal VEGF levels trigger pathophysiological changes in the choroid. We suggest that therapies to prevent vascular damage in diabetes must target both the retinal and choroidal vasculatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…14 In our earlier study, we sacrificed Kimba mice to examine, track, and localize changes in the fundus, retinal vasculature, and retinal morphology. 14,15,18,19 In these studies, we reported the existence of microaneurysm, venous dilatation, tortuosity, venous beading, and intraretinal microabnormalities in Kimba mice and we suggested that these features were similar to those observed in nonproliferative DR (NPDR) and RVO 20,21 in humans. Using the HRA+OCT imaging device, we not only confirmed the previous observations but for the first time we could follow the vascular, morphological, and retinal changes in real-time and within the same animal.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…14 In our earlier study, we sacrificed Kimba mice to examine, track, and localize changes in the fundus, retinal vasculature, and retinal morphology. 14,15,18,19 In these studies, we reported the existence of microaneurysm, venous dilatation, tortuosity, venous beading, and intraretinal microabnormalities in Kimba mice and we suggested that these features were similar to those observed in nonproliferative DR (NPDR) and RVO 20,21 in humans. Using the HRA+OCT imaging device, we not only confirmed the previous observations but for the first time we could follow the vascular, morphological, and retinal changes in real-time and within the same animal.…”
Section: Discussionmentioning
confidence: 59%
“…The results coincided with the previous histological work where the inner nuclear layer and outer retinal layers were thinner in comparison to control eyes. 18,19 The loss of cells in the inner retina of the Kimba mice is interesting, because although VEGF is not directly linked to photoreceptor loss, intraretinal and subretinal neovascularization have been associated with varying degrees of photoreceptor degeneration seen in macular telangiectasia and retinal angiomatous proliferation. 27,28 Although the blood vessels did not originate from the choroid but from the retinal vasculature in the Kimba mice, the process of photoreceptor loss observed in the Kimba mice is similar to wet AMD, whereby new fragile blood vessels grow into the photoreceptor outer segment layer and leak fluid and blood resulting in subsequent disintegration of the photoreceptor layer.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable to DR patients, neovascularization in both mouse models is observed in the retina and not in the choroid [119,126]. Preretinal neovascularization, which is a well-known human characteristic of proliferative DR [129], is not present in the Akimba or the Kimba model, given that the formation of new blood vessels is directed toward the VEGF-overexpressing photoreceptors in the outer retina [119].…”
Section: Transgenic Akimba Mouse Modelmentioning
confidence: 89%
“…The heterozygous Akita male mice develop features similar to early pathophysiological changes of diabetic complications, but fail to exhibit the advanced stage vascular dysfunctions. The non-diabetic Kimba (trVEGF029) mouse model, in which photoreceptors transiently overexpress hVEGF, is characterized by several early and advanced DR-associated vascular changes such as vascular permeability, capillary non-perfusion, microaneurysms and retinal neovascularization [119,[122][123][124][125][126][127]. It has been reported that the combination of high blood glucose levels and VEGF overexpression exacerbates the vascular complications in the Akimba mouse eye [119,127].…”
Section: Transgenic Akimba Mouse Modelmentioning
confidence: 99%
“…The Akimba mouse was generated by crossing two mouse strains. The Kimba mice, a nondiabetic model of proliferative retinopathy resulting from overexpression of Vegf driven by the rhodopsin promoter [121,122], were crossed with the diabetic Ins2…”
Section: Mouse Genetic Models Of Drmentioning
confidence: 99%